Modified oxygen-releasing nano peroxide for degrading organic pollutants, composite oxygen-releasing material, preparation method and application
By wrapping the pH adjuster and a specific film layer in the modified oxygen-releasing nanoperoxide, forming a double-film layer-encapsulated structure, the problems of low purity, poor dispersion, fast oxygen release speed, poor stability and great impact on the environmental pH value in the prior art are solved, and more stable oxygen release and better pH value maintenance are achieved.
Patent Information
- Application Number
- CN202411899337.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
When using modified nanoperoxides to repair groundwater organic pollution, the prior art has problems such as low purity, poor dispersion, fast oxygen release speed, poor stability and a large impact on environmental pH.
采用改性释氧纳米过氧化物,通过包裹释氧纳米过氧化物、pH调节剂、聚乙烯醇-聚(N-异丙基丙烯酰胺)膜层和交联壳聚糖膜层,形成特定膜层的双膜层包裹结构,显著减缓氧气的释放时间,提高水中的溶解氧含量和氧化还原电位,同时稳定性更好,对pH值几乎无影响。
The more stable release of modified oxygen-release nanoperoxides is achieved, the oxygen release time is extended, the dissolved oxygen content and redox potential in the water body are improved, the stability is better, and the environmental pH value is effectively maintained.
Smart Images

Figure CN119660939A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, in particular to a modified oxygen-releasing nanoperoxide for degrading organic pollutants, a composite slow-release oxygen material, a preparation method and an application thereof. Background Art
[0002] As a key link in the water resources system, groundwater plays an irreplaceable role in maintaining the steady development of the economy and society. However, due to improper treatment of industrial waste and urban garbage, abuse of agricultural fertilizers and pesticides, organic pollutants leak into the groundwater system, causing serious problems of groundwater organic pollution, posing a potential threat to people's production and life.
[0003] Currently, the main remediation methods for groundwater organic pollution include extraction treatment, in-situ aeration, in-situ chemical oxidation and permeable reaction wall technology. However, these remediation methods generally involve the use of a large amount of chemical agents, large-scale construction, and high operation and maintenance costs. They are often accompanied by the generation of secondary pollutants such as wastewater and waste gas, and are prone to tailing or rebound phenomena in the later stages of remediation.
[0004] In recent years, aerobic microbial degradation technology has attracted wide attention due to its advantages such as low disturbance, low cost and no secondary pollution. Among them, the level of dissolved oxygen (DO) in groundwater is considered to be a key factor affecting in situ bioremediation. Due to the low dissolved oxygen content in groundwater, it is difficult to support effective degradation by aerobic microorganisms. Therefore, calcium peroxide (CaO 2 ) and other solid oxygen-releasing compounds to supply oxygen to groundwater, which is considered to be a very promising oxygen delivery method. However, in actual application, it has a significant impact on the environmental pH value and the oxygen release rate is too fast, which has an adverse effect on the microbial growth environment and the organic matter degradation process, weakening the expected effect of in situ remediation. Summary of the invention
[0005] The purpose of the present invention is to provide a modified oxygen-releasing nanoperoxide, a composite slow-release oxygen material, a preparation method and an application for degrading organic pollutants. At least one of the problems of the modified nanoperoxide in the prior art, namely, low purity, poor dispersibility, fast oxygen release rate, poor stability and large impact on the pH value of the environment, is solved. The composite slow-release oxygen material of the present invention, on the basis of the modified nanoperoxide, further significantly slows down the release time of oxygen, increases the dissolved oxygen content in water, and the redox potential, can stably release oxygen for a long time, improves stability, and has almost no effect on the pH value.
[0006] To achieve the above objectives, this application provides the following technical solutions:
[0007] In a first aspect, a modified oxygen-releasing nanoperoxide for degrading organic pollutants is provided, comprising an oxygen-releasing nanoperoxide, a pH regulator, a polyvinyl alcohol-poly (N-isopropylacrylamide) film layer and a cross-linked chitosan film layer, wherein the polyvinyl alcohol-poly (N-isopropylacrylamide) film layer wraps the oxygen-releasing nanoperoxide and the pH regulator, and the cross-linked chitosan film layer wraps the polyvinyl alcohol-poly (N-isopropylacrylamide) film layer.
[0008] In the present invention, the modified oxygen-releasing nanoperoxide for degrading organic pollutants can release oxygen more stably, the oxygen release time can be longer, and the pH of the environment such as water bodies can be well maintained to avoid significant pH changes caused by the release of oxygen.
[0009] In one embodiment, the polyvinyl alcohol-poly (N-isopropylacrylamide) film layer is obtained by polymerizing poly (N-isopropylacrylamide) and polyvinyl alcohol; and / or, the cross-linked chitosan film layer is obtained by cross-linking chitosan and an aldehyde-containing compound.
[0010] In one embodiment, the particle size of the modified oxygen-releasing nanoperoxide is 10 nm to 500 nm, preferably 50 nm to 100 nm. The median particle size Dv of the modified oxygen-releasing nanoperoxide is 50 It is 50nm to 200nm, preferably 50nm to 100nm.
[0011] In one embodiment, the modified oxygen-releasing nanoperoxide further includes a dispersant and a stabilizer.
[0012] In one embodiment, the oxygen-releasing nanoperoxide includes at least one of nano-calcium peroxide, nano-magnesium peroxide, nano-sodium peroxide, and nano-potassium peroxide, preferably nano-calcium peroxide.
[0013] In one embodiment, the pH adjuster includes hydrogen phosphate and / or ammonium salt, preferably hydrogen phosphate and ammonium salt. Further, the mass ratio of the hydrogen phosphate to the ammonium salt is 1:(0.1-5), preferably 1:(1-3). Further, the hydrogen phosphate is selected from potassium dihydrogen phosphate and / or dipotassium hydrogen phosphate, preferably potassium dihydrogen phosphate, and the ammonium salt is selected from ammonium sulfate and / or ammonium chloride, preferably ammonium sulfate.
[0014] In one embodiment, the dispersant includes at least one of polyethylene glycol, sodium lauryl sulfate, and polyacrylamide, preferably polyethylene glycol. And / or, the stabilizer includes at least one of sodium citrate, citric acid, lactic acid, and sodium lactate, preferably sodium citrate.
[0015] Wherein, the polyethylene glycol is selected from polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600, preferably polyethylene glycol 200.
[0016] In a second aspect, a method for preparing the modified oxygen-releasing nanoperoxide for degrading organic pollutants according to the first aspect is provided, comprising:
[0017] (1) preparing an oxygen-releasing nanoperoxide emulsion A containing a pH regulator and polyvinyl alcohol;
[0018] (2) mixing chitosan, an aldehyde-containing compound, poly(N-isopropylacrylamide) and a dilute acid aqueous solution to obtain a solution B;
[0019] (3) adding the solution B to the oxygen-releasing nanoperoxide emulsion A, adjusting the pH value to 10-12, preferably 10-11, and reacting to obtain a modified oxygen-releasing nanoperoxide.
[0020] In one embodiment, in step (1), the oxygen-releasing nanoperoxide emulsion A containing a pH regulator and polyvinyl alcohol is prepared by adding hydrogen peroxide dropwise to an aqueous solution containing a soluble oxygen-releasing salt, a dispersant, a stabilizer, and ammonia water for reaction, and then adding a pH regulator and polyvinyl alcohol and mixing.
[0021] In one embodiment, in step (1), the mass ratio of the soluble oxygen-releasing salt, dispersant, stabilizer, ammonia water, hydrogen peroxide, pH adjuster, polyvinyl alcohol, and water is: 1: (0.05-0.5): (0.05-0.5): (1-6): (1-10): (0.1-5): (0.01-0.1): (2-10), preferably 1: (0.08-0.5): (0.08-0.5): (1-4): (1-5): (0.8-5): (0.008-0.05): (2-5).
[0022] In one embodiment, in step (1), the rate of adding hydrogen peroxide is 0.05 ml / min to 1 ml / min, preferably 0.1 to 0.5 ml / min.
[0023] In one embodiment, in step (1), the soluble oxygen-releasing salt is at least one of a soluble calcium salt, a soluble magnesium salt, a soluble sodium salt, a soluble potassium salt, etc. Further, the soluble calcium salt is selected from at least one of calcium chloride, calcium sulfate, calcium bicarbonate, and calcium nitrate, preferably calcium chloride. The soluble magnesium salt is selected from at least one of magnesium chloride, magnesium sulfate, magnesium bicarbonate, and magnesium nitrate, preferably magnesium chloride. The soluble sodium salt is selected from at least one of sodium chloride, sodium sulfate, sodium bicarbonate, and sodium nitrate, preferably sodium chloride. The soluble potassium salt is selected from at least one of potassium chloride, potassium sulfate, potassium bicarbonate, and potassium nitrate, preferably potassium chloride.
[0024] In one embodiment, in step (1), the dispersant is selected from at least one of polyethylene glycol, sodium lauryl sulfate, and polyacrylamide, preferably polyethylene glycol. The stabilizer is selected from at least one of sodium citrate, citric acid, lactic acid, and sodium lactate, preferably sodium citrate.
[0025] Wherein, the polyethylene glycol is selected from polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600, preferably polyethylene glycol 200.
[0026] In one embodiment, in step (1), the mass concentration of the ammonia water is 10% to 50%, preferably 10% to 30%.
[0027] In one embodiment, in step (1), the mass concentration of hydrogen peroxide is 10% to 50%, preferably 10% to 30%.
[0028] In one embodiment, in step (1), the pH regulator is selected from hydrogen phosphate and / or ammonium salt, preferably hydrogen phosphate and ammonium salt. Further, the mass ratio of the hydrogen phosphate and the ammonium salt is 1: (0.1-5), preferably 1: (1-3). Further, the hydrogen phosphate is selected from potassium dihydrogen phosphate and / or dipotassium hydrogen phosphate, preferably potassium dihydrogen phosphate, and the ammonium salt is selected from ammonium sulfate and / or ammonium chloride, preferably ammonium sulfate. In this process, the addition of a pH regulator not only effectively overcomes the problem of increased pH of the slow-release oxygen material when it comes into contact with water, but also can better maintain the pH of the environment, and can also provide the required nitrogen and phosphorus sources for the growth of microorganisms, thereby promoting long-term oxygen release.
[0029] In one embodiment, in step (1), the aqueous solution containing soluble oxygen-releasing salt, dispersant, stabilizer, and ammonia water can be prepared by conventional methods in the art. For example, calcium chloride is first added to water, stirred until dissolved, and then the dispersant, stabilizer, and ammonia water are added and mixed. Mixing can be performed by conventional methods in the art, such as stirring.
[0030] In one embodiment, in step (2), the mass ratio of chitosan, aldehyde-containing compound, poly(N-isopropylacrylamide) and dilute acid aqueous solution is (1-5):(0.01-1):(0.01-0.8):100, preferably (1-3):(0.1-0.5):(0.01-0.5):100.
[0031] In one embodiment, in step (2), the aldehyde-containing compound is at least one of formaldehyde, glutaraldehyde, glutaric anhydride, and succinic anhydride, preferably glutaraldehyde.
[0032] In one embodiment, in step (2), the dilute acid aqueous solution is selected from at least one of dilute hydrochloric acid aqueous solution, dilute sulfuric acid aqueous solution, dilute nitric acid aqueous solution and dilute citric acid aqueous solution. The molar concentration of the dilute acid aqueous solution is 0.1 mol / L to 4 mol / L, preferably 0.1 mol / L to 1.0 mol / L.
[0033] In one embodiment, in step (2), chitosan is first added to a dilute acid aqueous solution to dissolve it, and then the aldehyde-containing compound and poly (N-isopropylacrylamide) are added and mixed.
[0034] In one embodiment, in step (2), the mixing time is 2 min to 20 min, preferably 5 min to 15 min. The mixing method can be stirring, the stirring rate / speed is 100 rpm / min to 700 rpm / min, preferably 300 rpm / min to 500 rpm / min, and the stirring time is 2 min to 20 min, preferably 5 min to 15 min.
[0035] In one embodiment, the mass ratio of the solution B to the nanoperoxide emulsion A is 1:(1-10), preferably 1:(2-8), for example 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8.
[0036] The specific ratio of the raw materials in the above steps (1) and (2) of the present invention can achieve a better effect of modifying the oxygen-releasing nanoperoxide.
[0037] In one embodiment, in step (3), the solution B is added to the oxygen-releasing nanoperoxide emulsion A by dropwise addition. In the present invention, the dropwise addition method is more conducive to the release of oxygen and the maintenance of pH value of the prepared modified oxygen-releasing nanoperoxide. Furthermore, the dropwise addition rate is 0.05 to 1 ml / min, preferably 0.1 to 0.9 ml / min. When the dropwise addition speed is controlled within a specific rate range, the effect is more improved.
[0038] In one embodiment, in step (3), a dilute alkali aqueous solution is used to adjust the pH value. Preferably, the pH value is adjusted by dripping, for example, the dripping rate can be 0.1-1.5 mL / min. Further, the dilute alkali aqueous solution is selected from at least one of a dilute sodium hydroxide aqueous solution, a dilute potassium hydroxide aqueous solution and an ammonia aqueous solution. The mass concentration of the dilute alkali aqueous solution is 0.1 g / L to 10 g / L, preferably 2 g / L to 5 g / L.
[0039] In one embodiment, in step (3), the reaction time is 1 to 30 min, preferably 3 to 10 min.
[0040] In one embodiment, in step (3), after the reaction, before obtaining the modified oxygen-releasing nanoperoxide, solid-liquid separation, washing and drying are also performed. The solid-liquid separation can be carried out in a conventional manner in the art, such as centrifugation, suction filtration, etc., preferably centrifugation, further, the centrifugation condition is a centrifugal speed of 4000-6000rpm / min, a centrifugal time of 2-10min, preferably a centrifugal speed of 5000rpm / min, and a centrifugal time of 5min. The washing can be repeatedly rinsed with deionized water and / or an organic solvent, preferably first rinsed with deionized water, then rinsed with an organic solvent, further preferably, rinsed with deionized water 2-3 times, and rinsed with an organic solvent 2-3 times. The organic solvent is selected from one or more of ethanol, acetone, ether, and petroleum ether, preferably ethanol. The inventors have found that the use of this washing method can make the dispersion performance of the modified oxygen-releasing nanoperoxide better.
[0041] In one embodiment, in step (3), the drying temperature is 30 to 80° C., preferably 40 to 60° C., and the drying time is 4 to 24 hours, preferably 8 to 12 hours.
[0042] In a third aspect, a composite slow-release oxygen material is provided, comprising a modified oxygen-releasing nanoperoxide and a modified sodium alginate coating layer, wherein the modified sodium alginate coating layer wraps at least a portion of the modified oxygen-releasing nanoperoxide, wherein the modified oxygen-releasing nanoperoxide is the modified oxygen-releasing nanoperoxide described in the first aspect and / or the modified oxygen-releasing nanoperoxide prepared by the method described in the second aspect.
[0043] Wherein, the sodium alginate coating layer is obtained by cross-linking modified sodium alginate and soluble calcium salt.
[0044] In one embodiment, the modified sodium alginate is modified by 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA).
[0045] In a fourth aspect, a method for preparing the composite slow-release oxygen material described in the third aspect is provided, comprising loading a modified oxygen-releasing nanoperoxide into a cylindrical device having a grid, and then successively immersing the modified oxygen-releasing nanoperoxide in an aqueous solution of modified sodium alginate for a first time and in an aqueous solution of a soluble calcium salt for a second time, and drying to obtain the composite slow-release oxygen material, wherein the modified oxygen-releasing nanoperoxide is the modified oxygen-releasing nanoperoxide described in the first aspect and / or the modified oxygen-releasing nanoperoxide prepared by the method described in the second aspect.
[0046] In one embodiment, a grille is provided on the outer circumference of the cylindrical device, and a matching filter bag is built into the cylindrical device.
[0047] In one embodiment, the grille is composed of grille bars that are evenly staggered. Preferably, the grille is composed of grille bars that are staggered in parallel. Further preferably, the angle α between the staggered grille bars of the grille is 0 to 90°, preferably 30 to 90°; the spacing L between adjacent grille bars is 0.5 to 3 cm, preferably 1 to 2 cm; the width of the grille bars is 0.1 to 0.5 cm, preferably 0.1 to 0.2 cm. When the parameters of the grille are within the above preferred range, the prepared composite slow-release oxidizing material for degrading organic pollutants can more effectively slow down the release of oxygen in water, increase the dissolved oxygen and redox potential in the water, and have better stability.
[0048] In one embodiment, the cylindrical device is cylindrical, and the diameter-to-height ratio D / H of the cylindrical device is 0.1 to 0.5, preferably 0.1 to 0.3. The diameter-to-height ratio refers to the ratio between the diameter and the height of the cylindrical device. Preferably, the diameter D of the cylindrical device is 1 to 10 cm, preferably 3 to 6 cm, and the height H of the cylindrical device is 1 to 100 cm, preferably 20 to 50 cm.
[0049] In one embodiment, both ends of the cylindrical device with the grid are connected.
[0050] In one embodiment, the top of the outer peripheral surface has an external thread, and the bottom of the outer peripheral surface has an internal thread. A plurality of cylindrical devices with grids can be connected by threads. For example, the top of cylindrical device A with grids and the bottom of cylindrical device B with grids are connected by threads, the top of cylindrical device B with grids and the bottom of cylindrical device C with grids are connected by threads, and so on. The number of connections is not limited.
[0051] In one embodiment, the grid bars may be metal wires. Further preferably, the metal wires may be at least one of stainless steel wires, iron wires, copper wires, aluminum wires, titanium wires, etc., preferably stainless steel wires.
[0052] In one embodiment, the mesh size of the filter bag is 50-500 mesh, preferably 100-300 mesh.
[0053] In one embodiment, the adaptation may refer to that the shape and size of the filter bag and the shape and size of the cylindrical device with the grid differ by no more than ±0.5 cm.
[0054] In one embodiment, the filter bag may be made of polyester fiber, polypropylene, nylon, glass fiber, etc. The filter bag may be sealed with a drawstring.
[0055] In one embodiment, the first immersion temperature is room temperature, and the first immersion time is 1 to 120 minutes, preferably 10 minutes to 60 minutes. The second immersion temperature is room temperature, and the second immersion time is 1 to 120 minutes, preferably 10 minutes to 60 minutes. The first immersion and the second immersion are not specifically limited, and the cylindrical device with the grid only needs to be completely immersed in the sodium alginate aqueous solution and / or the soluble calcium salt aqueous solution.
[0056] In one embodiment, the mass concentration of the aqueous solution of modified sodium alginate is 1 g / L to 50 g / L, preferably 5 g / L to 30 g / L. The mass concentration of the aqueous solution of soluble calcium salt is 1 g / L to 50 g / L, preferably 5 g / L to 40 g / L.
[0057] In one embodiment, the preparation method of the modified sodium alginate comprises: stirring 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA), sulfuric acid, sodium alginate and water in a water bath at 80° C. to 150° C. for 2 h to 8 h.
[0058] In one embodiment, the mass ratio of 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA), sulfuric acid, sodium alginate and water is 1:(0.01-1.5):(1-5):(10-500), preferably 1:(0.05-1):(1-3):(50-200).
[0059] In one embodiment, the molar concentration of the sulfuric acid is 1 to 5 mol / L, preferably 2 to 4 mol / L.
[0060] In one embodiment, the soluble calcium salt is selected from at least one of calcium chloride, calcium sulfate, and calcium bicarbonate, preferably calcium chloride.
[0061] In one embodiment, the drying temperature is 20-60°C, preferably 30-40°C, and the drying time is 4h-24h, preferably 8h-12h. For example, air drying can be adopted, and the air drying conditions are ventilated, and the temperature is 20-35°C, and the drying time is 4h-24h, preferably 30-35°C, and the drying time is 8h-12h.
[0062] In the present invention, the reaction temperature not mentioned can be carried out at room temperature.
[0063] In the present invention, the room temperature is 20-35°C, preferably 20-30°C.
[0064] In the fifth aspect, a cylindrical device with a grid is provided, which is applied to the method for preparing the composite slow-release oxygen material in the fourth aspect, and is characterized in that a grid is arranged on the outer peripheral surface of the cylindrical device, and a matching filter bag is built into the cylindrical device.
[0065] In one embodiment, a grille is provided on the outer circumference of the cylindrical device, and a matching filter bag is built into the cylindrical device.
[0066] In one embodiment, the grille is composed of grille bars that are evenly staggered. Preferably, the grille is composed of grille bars that are staggered in parallel. Further preferably, the angle α between the staggered grille bars of the grille is 0 to 90°, preferably 30 to 90°; the spacing L between adjacent grille bars is 0.5 to 3 cm, preferably 1 to 2 cm; the width of the grille bars is 0.1 to 0.5 cm, preferably 0.1 to 0.2 cm. When the parameters of the grille are within the above preferred range, the prepared composite slow-release oxidizing material for degrading organic pollutants can more effectively slow down the release of oxygen in water, increase the dissolved oxygen and redox potential in the water, and have better stability.
[0067] In one embodiment, the cylindrical device is cylindrical, and the diameter-to-height ratio D / H of the cylindrical device is 0.1 to 0.5, preferably 0.1 to 0.3. The diameter-to-height ratio refers to the ratio between the diameter and the height of the cylindrical device. Preferably, the diameter D of the cylindrical device is 1 to 10 cm, preferably 3 to 6 cm, and the height H of the cylindrical device is 1 to 100 cm, preferably 20 to 50 cm.
[0068] In one embodiment, both ends of the cylindrical device with the grid are connected.
[0069] In one embodiment, the top of the outer peripheral surface has an external thread, and the bottom of the outer peripheral surface has an internal thread. A plurality of cylindrical devices with grids can be connected by threads. For example, the top of cylindrical device A with grids and the bottom of cylindrical device B with grids are connected by threads, the top of cylindrical device B with grids and the bottom of cylindrical device C with grids are connected by threads, and so on. The number of connections is not limited.
[0070] In one embodiment, the grid bars may be metal wires. Further preferably, the metal wires may be at least one of stainless steel wires, iron wires, copper wires, aluminum wires, titanium wires, etc., preferably stainless steel wires.
[0071] In one embodiment, the mesh size of the filter bag is 50-500 mesh, preferably 100-300 mesh.
[0072] In one embodiment, the adaptation may refer to that the shape and size of the filter bag and the shape and size of the cylindrical device with the grid differ by no more than ±0.5 cm.
[0073] In one embodiment, the filter bag may be made of polyester fiber, polypropylene, nylon, glass fiber, etc. The filter bag may be sealed with a drawstring.
[0074] In a sixth aspect, there is provided application of the modified oxygen-releasing nanoperoxide and / or composite slow-release oxygen material for degrading organic pollutants in the remediation of soil and / or groundwater containing organic pollutants.
[0075] In one embodiment, the organic pollutants include at least one of petroleum hydrocarbons, polycyclic aromatic hydrocarbons, and benzene series.
[0076] Compared with the prior art, the beneficial effects of this application are:
[0077] (1) The oxygen-releasing nanoperoxide and pH regulator of the present invention are both wrapped, and are respectively and sequentially wrapped by a polyvinyl alcohol-poly (N-isopropylacrylamide) film layer and a cross-linked chitosan film layer to form a modified oxygen-releasing nanoperoxide wrapped by a double film layer of a specific film layer, and the oxygen-releasing nanoperoxide, the pH regulator and the specific film layer achieve a mutual coordination effect, which significantly increases the stability of the modified oxygen-releasing nanoperoxide, makes the oxygen release time more durable, and better maintains the pH of the environment. Moreover, the oxygen-releasing nanoperoxide of the present invention also reaches the nanometer level in a cross-linked state, with a particle size of about 10nm to 500nm, and a median particle size Dv50 of 50nm to 200nm.
[0078] (2) In the present invention, in step 1, metal salt, dispersant, hydrogen peroxide, ammonia water, stabilizer, polymer 1 and pH regulator are used to form emulsion A. In step 2, chitosan, crosslinking agent and polymer 2 are used to form solution B. In step 3, solution B is dripped into solution A to form modified nano calcium peroxide. When solution B is dripped into solution A, polymer A and polymer B will form a layer of coated polyvinyl alcohol-poly (N-isopropylacrylamide) film layer, which plays an embedding role for oxygen-releasing nano peroxide and pH regulator. The addition of alkaline chitosan and crosslinking agent will form two layers of coated crosslinked chitosan film layer. The modified oxygen-releasing nano peroxide prepared according to the method of the present invention has a large coating amount, high calcium peroxide purity, good dispersibility, and prolonged sustained release time. The addition of pH regulator not only overcomes the problem of pH increase of sustained oxygen-releasing material when it comes into contact with water, but also provides the required nitrogen source and phosphorus source for microbial growth, and has the functions of long-term oxygen release and pH regulation.
[0079] (3) The modified nanoperoxide is loaded into a filter bag, and then loaded into the cylindrical device with a grid of the present invention, and then the modified nanoperoxide is soaked three times for coating to form a special form of three-layer coating, which is placed in the monitoring well as an oxygen source well in the form of this device, which not only significantly slows down the oxygen release time, but also increases the dissolved oxygen content and redox potential in the groundwater, and has better stability. In addition, the use of hydrophobic modified sodium alginate reduces the solubility of the coating in water and prolongs the action time of the three-layer coating in water.
[0080] (4) The cylindrical device with a grid grid of the present invention is suitable for most soil-groundwater monitoring wells (for example, with a diameter of 6.3 cm), and can also be loaded in a modular manner. It has the advantages of simple operation and easy promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] Figure 1 This is a SEM image of the modified nano calcium peroxide proposed in Example 1 of the present application;
[0082] Figure 2 This is a SEM image of commercially available calcium peroxide proposed in Comparative Example 4 of the present application;
[0083] Figure 3 This is a TEM image of the modified nano calcium peroxide proposed in Example 1 of the present application;
[0084] Figure 4 This is a TEM image of commercially available calcium peroxide proposed in Comparative Example 4 of the present application;
[0085] Figure 5 XRD diagram of the modified nano calcium peroxide proposed in Example 1 of the present application and the calcium peroxide proposed in Comparative Example 4; in the figure, CaO 2 Refers to the calcium peroxide of Comparative Example 4, pH / CS / Nano-CaO 2 Refers to the modified nano calcium peroxide obtained in Example 1;
[0086] Figure 6 This is a schematic structural diagram of a cylindrical device with a grid proposed in Example 4 of the present application;
[0087] Figure 7 This is a schematic diagram of the loading of the modified nano calcium peroxide proposed in Example 4 of the present application;
[0088] Figure 6 and Figure 7 The reference numerals are as follows: 1-outer peripheral surface; 11-grid; 12-external thread; 111-grid bar; 2-filter bag; 21-drawstring;
[0089] Figure 8 The curve of the dissolved oxygen content in water of the composite slow-release oxygen materials proposed in Examples 4-6 and Comparative Examples 5-9 of the present application over time;
[0090] Fig. 9 The pH change curve of the composite slow-release oxygen material in water body over time proposed in Examples 4-6 and Comparative Examples 5-9 of the present application;
[0091] Fig.10 This is a curve showing the change of the redox potential of the composite slow-release oxygen material in water over time as proposed in Examples 4-6 and Comparative Examples 5-9 of the present application. DETAILED DESCRIPTION
[0092] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0093] If no specific experimental steps or conditions are specified in the examples, the experiments can be carried out according to the conventional steps or conditions described in the literature in the art.
[0094] Unless otherwise specified, all reagents and raw materials used in the examples are commercially available products.
[0095] Among them, the filter bag was purchased from Zhongting Environmental Protection, model NMOZT-200 mesh-50*1000.
[0096] In the present invention, a Japanese JEOL-7800 field emission scanning electron microscope (SEM) is used to observe the morphology and particle size of the sample.
[0097] In the present invention, a Japanese JEM-2100F transmission electron microscope (TEM) was used to observe the morphology and dispersion of the samples.
[0098] In the present invention, a German Bruker D8 X-ray diffractometer (XRD) is used to identify the composition and structure of the sample. The test conditions are CuKα radiation, Ni filter, tube voltage 40kV, tube current 40mA, and scanning speed 2° / min.
[0099] It should be noted that, in the description of the present application, the terms "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating directions or positional relationships, are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description. They do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present application.
[0100] Furthermore, it should be understood that for the sake of ease of description, the sizes of the various components shown in the drawings are not drawn according to actual proportions. For example, the thickness or width of certain layers may be exaggerated relative to other layers.
[0101] It should be noted that like reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined or described in one drawing, it will not require further detailed discussion and description in the description of the subsequent drawings.
[0102] like Figure 6-7 As shown, this embodiment provides a cylindrical device with a grid, a grid 11 is arranged on the outer peripheral surface 1 of the cylindrical device, and an adapted filter bag 2 is built into the cylindrical device.
[0103] Furthermore, the grille 11 is evenly staggered with grille bars 111. Preferably, the grille 11 is staggered with grille bars 111 arranged in parallel. Further preferably, the angle α between the staggered grille bars 111 of the grille 11 is 0 to 90°, preferably 30 to 90°; the spacing L between adjacent grille bars 111 is 0.5 to 2 cm, preferably 1 to 2 cm; the width of the grille bars 111 is 0.1 to 0.5 cm, preferably 0.1 to 0.2 cm. When the parameters of the grille 11 are within the preferred range, the prepared composite slow-release oxidant for degrading organic pollutants can more effectively slow down the release of oxygen, increase the dissolved oxygen and redox potential in the water body, and have better stability.
[0104] Further, the cylindrical device is cylindrical, and the diameter-to-height ratio D / H of the cylindrical device is 0.1 to 0.5, preferably 0.1 to 0.3. The diameter-to-height ratio refers to the ratio between the diameter and the height of the cylindrical device. Preferably, the diameter D of the cylindrical device is 1 to 10 cm, preferably 3 to 6 cm, and the height H of the side is 1 to 100 cm, preferably 20 to 50 cm.
[0105] Furthermore, both ends of the cylindrical device with the grid are connected.
[0106] Furthermore, the top of the outer peripheral surface 1 has an external thread 12, and the bottom of the outer peripheral surface 1 has an internal thread. A plurality of cylindrical devices with grids can be connected by threads. For example, the top of cylindrical device A with grids and the bottom of cylindrical device B with grids are connected by threads, the top of cylindrical device B with grids and the bottom of cylindrical device C with grids are connected by threads, and so on. The number of connections is not limited.
[0107] Furthermore, the grid bar 111 is a metal wire, and the metal wire may be at least one of stainless steel wire, iron wire, copper wire, aluminum wire, titanium wire, etc., preferably stainless steel wire.
[0108] Furthermore, the mesh number of the filter bag is 50-500 mesh, preferably 100-300 mesh.
[0109] Furthermore, the adaptation may refer to that the shape and size of the filter bag and the shape and size of the cylindrical device with the grid differ by no more than ±0.5 cm.
[0110] Furthermore, the filter bag is made of polyester fiber, polypropylene, nylon, glass fiber, etc. The filter bag can be sealed with a drawstring.
[0111] Example 1
[0112] This embodiment provides a modified oxygen-releasing nanoperoxide for degrading organic pollutants, and the preparation method is as follows:
[0113] (1) 11.1 g of calcium chloride was added to 25 g of deionized water and stirred until dissolved. Then, 1 g of dispersant polyethylene glycol 200, 1 g of stabilizer sodium citrate and 35 g of concentrated ammonia water with a mass concentration of 30% were added and stirred until dissolved. Then, 50 g of hydrogen peroxide with a mass concentration of 30% was dripped into the above solution at 0.2 mL / min to react. After the dripping was completed, 10 g of pH adjuster (5 g of potassium dihydrogen phosphate and 5 g of ammonium sulfate) and 0.1 g of polyvinyl alcohol were added and stirred until dissolved to form an emulsion A.
[0114] (2) 0.5 g of chitosan was added to 50 g of 1.0 mol / L hydrochloric acid, and after stirring to dissolve, 0.1 g of glutaraldehyde and 0.1 g of poly (N-isopropylacrylamide) were added, and the mixture was stirred at 300 rppm / min for 10 min to form solution B.
[0115] (3) Solution B was dripped into emulsion A at a rate of 0.2 mL / min to form solution C, and a sodium hydroxide solution with a mass concentration of 2 g / L was dripped into solution C at a rate of 0.5 mL / min to adjust the pH of solution C to 10, and the reaction was carried out for 5 min, and then centrifuged at a speed of 5000 rpm / min for 5 min to obtain a solid mixture, and the obtained solid mixture was first washed twice with deionized water, then washed twice with ethanol, and dried at 60° C. for 8 h to obtain modified nano calcium peroxide.
[0116] The morphology and particle size of the modified nano calcium peroxide in this embodiment were observed using a Japanese JEOL-7800 field emission scanning electron microscope (SEM). Figure 1 shown.
[0117] The morphology and dispersibility of the modified nano calcium peroxide in this example were observed using a Japanese JEM-2100F transmission electron microscope (TEM). Figure 3 shown.
[0118] The composition structure of the modified nano calcium peroxide in this embodiment was observed using a German Bruker D8 X-ray diffractometer (XRD). Figure 4 shown.
[0119] Example 2
[0120] This embodiment provides a modified oxygen-releasing nanoperoxide for degrading organic pollutants, and the preparation method is as follows:
[0121] (1) 11.1 g of calcium chloride was added to 25 g of deionized water and stirred until dissolved. Then, 5 g of dispersant polyethylene glycol 200, 1 g of stabilizer sodium citrate and 35 g of concentrated ammonia water with a mass concentration of 30% were added and stirred until dissolved. Then, 50 g of hydrogen peroxide with a mass concentration of 30% was dripped into the solution at 0.2 mL / min to react. After the dripping was completed, 20 g of pH adjuster (10 g of potassium dihydrogen phosphate and 10 g of ammonium sulfate) and 0.2 g of polyvinyl alcohol were added and stirred until dissolved to form an emulsion A.
[0122] (2) 1 g of chitosan was added to 50 g of 1.0 mol / L hydrochloric acid, and after stirring to dissolve, 0.2 g of glutaraldehyde and 0.2 g of poly (N-isopropylacrylamide) were added, and stirred at 300 rppm for 10 min to form solution B.
[0123] (3) Solution B was dripped into emulsion A at a rate of 0.2 mL / min to form solution C, and a sodium hydroxide solution with a mass concentration of 2 g / L was dripped into solution C at a rate of 0.5 mL / min to adjust the pH of solution C to 11, and the reaction was carried out for 3 min, and then centrifuged at a speed of 5000 rpm / min for 5 min to obtain a solid mixture, and the obtained solid mixture was first washed twice with deionized water, then washed twice with ethanol, and dried at 60° C. for 8 h to obtain modified nano calcium peroxide.
[0124] Example 3
[0125] The same as Example 1, the only difference is that the amount of glutaraldehyde added in step (2) is 0.5 g.
[0126] Comparative Example 1
[0127] The same as Example 1, except that glutaraldehyde is not added in step (2).
[0128] Comparative Example 2
[0129] The same as Example 1, the only difference is that in step (3), solution B is dripped into emulsion A at 5 mL / min to form solution C.
[0130] Comparative Example 3
[0131] The same as Example 1, except that polyvinyl alcohol is not added in step (1) and poly(N-isopropylacrylamide) is not added in step (2).
[0132] Comparative Example 4
[0133] Commercially available calcium peroxide (purchased from Foshan Nongxin Biotechnology Co., Ltd.) has a calcium peroxide content of 50-60%.
[0134] The morphology and particle size of the calcium peroxide were observed using a Japanese JEOL-7800 field emission scanning electron microscope (SEM). Figure 2 shown.
[0135] The morphology and dispersibility of the calcium peroxide were observed using a Japanese JEM-2100F transmission electron microscope (TEM). Figure 4 shown.
[0136] The composition structure of calcium peroxide was observed using a German Bruker D8 X-ray diffractometer (XRD). Figure 5 shown.
[0137] Test Example 1
[0138] The calcium peroxide content of the products prepared in the examples and comparative examples was measured according to the potassium permanganate titration method in the standard "HG / T 4505-2013 Industrial Calcium Peroxide". The measurement results are shown in Table 1.
[0139] Table 1 Calcium peroxide content
[0140] Example Calcium peroxide content% Example 1 81% Example 2 75% Example 3 65% Comparative Example 1 61% Comparative Example 2 21% Comparative Example 3 58% Comparative Example 4 52%
[0141] Application Example 1
[0142] 500 mL of 0.3 g / L sodium sulfite solution was prepared, the initial dissolved oxygen content was 0.05 mg / L, the pH was 7.42, 2 g of samples of Examples 1-3 and Comparative Examples 1-4 were used, and the column experiment was carried out for 1 day at a flow rate of 1 mL / min. The dissolved oxygen content and pH value after 1 day are shown in Table 2.
[0143] Table 2 Dissolved oxygen content and pH
[0144] Example Dissolved oxygen content (mg / L) pH Example 1 3.21 6.81 Example 2 2.82 7.20 Example 3 1.81 8.21 Comparative Example 1 1.19 8.94 Comparative Example 2 0.12 9.01 Comparative Example 3 1.23 9.32 Comparative Example 4 0.32 12.34
[0145] Example 4
[0146] This embodiment provides a composite slow-release oxygen material for degrading organic pollutants, and the preparation method is as follows:
[0147] Modified sodium alginate was prepared by the method of stirring 1 g 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA), 1 g sulfuric acid with a molar concentration of 4 mol / L, 2 g sodium alginate and 50 g deionized water in a water bath at 100°C for 2 h. According to steps (1)-(3) of Example 1, 1 kg of modified nano calcium peroxide was prepared. 1 kg of modified nano calcium peroxide was loaded into a filter bag of NMOZT-200 mesh-50*1000. The filter bag was loaded into a cylindrical device with a grid, and then put into a 10 g / L modified sodium alginate aqueous solution so that the modified sodium alginate aqueous solution covered the cylindrical device with a grid. After soaking at room temperature for 30 min, it was taken out and then put into 10 g / L CaCl 2 In aqueous solution, CaCl 2 The aqueous solution was submerged in a cylindrical device with a grid, immersed at room temperature for 30 minutes, and air-dried at 30°C for 8 hours to obtain a composite slow-release oxygen material for degrading organic pollutants.
[0148] Wherein, the cylindrical device with a grid is as follows Figure 6 As shown, the two ends of the cylindrical device with a grid are connected, and a grid 11 is arranged on the outer peripheral surface 1 of the cylindrical device. The grid 11 is staggered by grid bars 111 arranged evenly and parallelly, and the grid bars 111 are stainless steel wires. The angle α between the staggered stainless steel wires 111 of the grid 11 is 90°, and the spacing L between adjacent stainless steel wires 111 is 1 cm; the diameter of the stainless steel wire 111 is 0.1 cm. The cylindrical device is cylindrical, the diameter D of the cylindrical device is 5 cm, and the height H of the cylindrical device is 20 cm. The top of the outer peripheral surface 1 has an external thread 12, and the bottom of the outer peripheral surface 1 has an internal thread.
[0149] In this embodiment, the modified nano calcium peroxide is uniformly loaded into a filter bag, and the filter bag is loaded into five cylindrical devices with grids (such as Figure 7 As shown), the five cylindrical devices with grids can be connected end to end (i.e., the top surface of the first cylindrical device and the bottom of the second cylindrical device are connected together by threads, the top surface of the second cylindrical device and the bottom of the third cylindrical device are connected together by threads, and so on).
[0150] Example 5
[0151] This embodiment provides a composite slow-release oxygen material for degrading organic pollutants, and the preparation method is as follows:
[0152] The same as Example 4, except that the modified sodium alginate solution of 30 g / L was placed in the cylindrical device with the grid, and the sodium alginate solution was soaked for 60 min at room temperature, then taken out and 40 g / L CaCl 2 In aqueous solution, CaCl2 The aqueous solution submerged the cylindrical device with the grid, was immersed in the solution at room temperature for 60 minutes, and air-dried at 30°C for 12 hours to obtain a composite slow-release oxygen material for degrading organic pollutants.
[0153] Example 6
[0154] The same as the embodiment 4, the only difference is that the spacing L between the stainless steel wires 111 is 3 cm.
[0155] Comparative Example 5
[0156] The same as Example 4, the only difference is that the prepared 1kg modified nano calcium peroxide is put into a filter bag of NMOZT-200 mesh-50*1000, not into a cylindrical device with a grid, but directly into a 10g / L modified sodium alginate aqueous solution, so that the modified sodium alginate aqueous solution does not cover the filter bag, soaked at room temperature for 30 minutes, taken out, and then put into 10g / L CaCl 2 In aqueous solution, CaCl 2 The aqueous solution was filtered through a filter bag, soaked at room temperature for 30 minutes, and air-dried at 30°C for 8 hours to obtain nano calcium peroxide, a composite slow-release oxygen material for degrading organic pollutants.
[0157] Comparative Example 6
[0158] The same as Example 4, the only difference is that the prepared 1 kg modified nano calcium peroxide is not filled into a filter bag or a cylindrical device with a grid, but is directly placed in a 10 g / L modified sodium alginate aqueous solution, stirred at room temperature for 30 min, taken out, and dripped with 10 g / L CaCl 2 The solution was stirred for 30 min and dried at 30°C for 8 h to obtain a composite slow-release oxygen material for degrading organic pollutants.
[0159] Comparative Example 7
[0160] The same as Example 4, the only difference is that the filter bag is filled with the modified oxygen-releasing nanoperoxide prepared according to Comparative Example 1.
[0161] Comparative Example 8
[0162] The same as Example 4, the only difference is that paraffin is used instead of modified sodium alginate as the coating liquid.
[0163] Comparative Example 9
[0164] The same as Example 4, the only difference is that the filter bag is filled with the commercially available calcium peroxide in Comparative Example 4, and no subsequent treatment is performed after being placed in the cylindrical device.
[0165] Application Example 2
[0166] The composite slow-release oxygen materials (1 kg of composite slow-release oxygen material plus a cylindrical device) obtained in the above Examples 4-6 and Comparative Examples 7-9, the composite slow-release oxygen material (1 kg of composite slow-release oxygen material plus a filter bag) obtained in Comparative Example 5, and the composite slow-release oxygen material (1 kg of composite slow-release oxygen material filled in the cylindrical device described in Example 4) obtained in Comparative Example 6 were respectively placed in a groundwater monitoring well, and different time periods were set to measure the dissolved oxygen (DO), oxidation-reduction potential (ORP), and pH value in the well. The relevant parameters changed over time as shown in FIG. Figure 8-Figure 10 shown.
[0167] Among them, the detection of dissolved oxygen (DO), oxidation-reduction potential (ORP), and pH value was determined using the American Eureka Easy Probe EP20 five-parameter water quality analyzer.
[0168] from Figure 8-Figure 10 It can be seen that the composite slow-release oxygen material prepared by the comparative method begins to fail in a short time after being put into use and basically no longer releases oxygen; the composite slow-release oxygen material for degrading organic pollutants prepared by the method of the present invention can maintain the dissolved oxygen content in groundwater at 2 mg / L for a long time, and the maintenance time can be as long as 180 days, which significantly improves the stability of the composite slow-release oxygen material.
[0169] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A modified oxygen-releasing nanoperoxide for degrading organic pollutants, characterized in that: The invention comprises an oxygen-releasing nanoperoxide, a pH regulator, a polyvinyl alcohol-poly (N-isopropylacrylamide) film layer and a cross-linked chitosan film layer, wherein the polyvinyl alcohol-poly (N-isopropylacrylamide) film layer wraps the oxygen-releasing nanoperoxide and the pH regulator, and the cross-linked chitosan film layer wraps the polyvinyl alcohol-poly (N-isopropylacrylamide) film layer.
2. The modified oxygen-releasing nanoperoxide according to claim 1, characterized in that: The polyvinyl alcohol-poly (N-isopropylacrylamide) film layer is obtained by polymerizing poly (N-isopropylacrylamide) and polyvinyl alcohol; and / or, the cross-linked chitosan film layer is obtained by cross-linking chitosan and an aldehyde-containing compound; and / or, the particle size of the modified oxygen-releasing nanoperoxide is 10 nm to 500 nm, preferably 50 nm to 100 nm; and / or, the median particle size Dv of the modified oxygen-releasing nanoperoxide is 50 50nm to 200nm, preferably 50nm to 100nm; And / or, the oxygen-releasing nanoperoxide comprises at least one of nano calcium peroxide, nano magnesium peroxide, nano sodium peroxide, and nano potassium peroxide, preferably nano calcium peroxide; And / or, the pH adjuster comprises hydrogen phosphate and / or ammonium salt, preferably hydrogen phosphate and ammonium salt, and further, the mass ratio of the hydrogen phosphate to the ammonium salt is 1:(0.1-5), preferably 1:(1-3); And / or, the modified oxygen-releasing nanoperoxide further comprises a dispersant and a stabilizer.
3. A method for preparing a modified oxygen-releasing nanoperoxide for degrading organic pollutants, comprising: (1) preparing an oxygen-releasing nanoperoxide emulsion A containing a pH regulator and polyvinyl alcohol; (2) mixing chitosan, an aldehyde-containing compound, poly(N-isopropylacrylamide) and a dilute acid aqueous solution to obtain a solution B; (3) adding the solution B to the oxygen-releasing nanoperoxide emulsion A, adjusting the pH value to 10-12, preferably 10-11, and reacting to obtain a modified oxygen-releasing nanoperoxide.
4. The method for preparing the modified oxygen-releasing nanoperoxide according to claim 3, characterized in that: In step (1), the oxygen-releasing nanoperoxide emulsion A containing a pH regulator and polyvinyl alcohol is prepared by dropwise adding hydrogen peroxide to an aqueous solution containing a soluble oxygen-releasing salt, a dispersant, a stabilizer, and ammonia water for reaction, and then adding a pH regulator and polyvinyl alcohol and mixing; Preferably, the mass ratio of the soluble oxygen-releasing salt, dispersant, stabilizer, ammonia water, hydrogen peroxide, pH adjuster, polyvinyl alcohol and water is: 1: (0.05-0.5): (0.05-0.5): (1-6): (1-10): (0.1-5): (0.01-0.1): (2-10), preferably 1: (0.08-0.5): (0.08-0.5): (1-4): (1-5): (0.8-5): (0.008-0.05): (2-5); And / or, in step (1), the rate of adding hydrogen peroxide is 0.05 ml / min to 1 ml / min, preferably 0.1 to 0.5 ml / min. And / or, in step (1), the pH adjuster is selected from hydrogen phosphate and / or ammonium salt, preferably hydrogen phosphate and ammonium salt; further, the mass ratio of the hydrogen phosphate to the ammonium salt is 1:(0.1-5), preferably 1:(1-3).
5. The method for preparing the modified oxygen-releasing nanoperoxide according to claim 3, characterized in that: In step (2), the mass ratio of chitosan, aldehyde-containing compound, poly(N-isopropylacrylamide) and dilute acid aqueous solution is (1-5): (0.01-1): (0.01-0.8): 100, preferably (1-3): (0.1-0.5): (0.01-0.5): 100; and / or, the aldehyde-containing compound is at least one of formaldehyde, glutaraldehyde, glutaric anhydride and succinic anhydride, preferably glutaraldehyde; And / or, the mixing time is 2 min to 20 min, preferably 5 min to 15 min. And / or, the mass ratio of the solution B to the nanoperoxide emulsion A is 1:(1-10), preferably 1:(2-8).
6. The method for preparing the modified oxygen-releasing nanoperoxide according to claim 3, characterized in that: In step (3), the solution B is added to the oxygen-releasing nanoperoxide emulsion A by dropwise addition. Preferably, the dropwise addition rate is 0.05 to 1 ml / min, preferably 0.1 to 0.9 ml / min. And / or, in step (3), the reaction time is 1 to 30 min, preferably 3 to 10 min. And / or, in step (3), after the reaction and before obtaining the modified oxygen-releasing nanoperoxide, solid-liquid separation, washing and drying are further performed, wherein the washing is performed by repeated rinsing with deionized water and / or an organic solvent, preferably first rinsing with deionized water and then rinsing with an organic solvent.
7. A composite slow-release oxygen material, comprising a modified oxygen-releasing nanoperoxide and a modified sodium alginate coating layer, wherein the modified sodium alginate coating layer wraps at least a portion of the modified oxygen-releasing nanoperoxide, wherein the modified oxygen-releasing nanoperoxide is the modified oxygen-releasing nanoperoxide described in any one of claims 1 to 3 and / or the modified oxygen-releasing nanoperoxide prepared by the method described in any one of claims 4 to 6. Preferably, the sodium alginate coating layer is obtained by cross-linking modified sodium alginate and soluble calcium salt.
8. A method for preparing a composite slow-release oxygen material, comprising loading a modified oxygen-releasing nanoperoxide into a cylindrical device with a grid and a built-in filter bag, and then successively immersing the modified oxygen-releasing nanoperoxide in an aqueous solution of modified sodium alginate for a first time and in an aqueous solution of a soluble calcium salt for a second time, and drying to obtain the composite slow-release oxygen material, wherein the modified oxygen-releasing nanoperoxide is the modified oxygen-releasing nanoperoxide described in any one of claims 1 to 3 and / or the modified oxygen-releasing nanoperoxide prepared by the method described in any one of claims 4 to 6.
9. The method for preparing the composite slow-release oxygen material according to claim 8, characterized in that: A grille is arranged on the outer peripheral surface of the cylindrical device, and a matching filter bag is built into the cylindrical device; Preferably, the grille is composed of grille bars evenly staggered; Further preferably, the grille is staggered by grille bars arranged in parallel; More preferably, the angle α between the staggered grid bars of the grid is 0-90°, preferably 30-90°; the spacing L between adjacent grid bars is 0.5-3 cm, preferably 1-2 cm; the width of the grid bar is 0.1-0.5 cm, preferably 0.1-0.2 cm; Preferably, the diameter-to-height ratio D / H of the cylindrical device is 0.1 to 0.5, preferably 0.1 to 0.3; Preferably, both ends of the cylindrical device with the grid are connected; Preferably, the top of the outer peripheral curved surface has an external thread, the bottom of the outer peripheral curved surface has an internal thread, and a plurality of cylindrical devices with grids can be connected by threads; Preferably, the grid bar is a metal wire, preferably, the metal wire is at least one of stainless steel wire, iron wire, copper wire, aluminum wire, titanium wire, etc., preferably stainless steel wire; And / or, the mesh size of the filter bag is 50-500 mesh, preferably 100-300 mesh; And / or, the first immersion temperature is room temperature, the first immersion time is 1 to 120 min, preferably 10 min to 60 min; the second immersion temperature is room temperature, the second immersion time is 1 to 120 min, preferably 10 min to 60 min; And / or, the mass concentration of the aqueous solution of modified sodium alginate is 1g / L to 50g / L, preferably 5g / L to 30g / L; and / or, the mass concentration of the aqueous solution of soluble calcium salt is 1g / L to 50g / L, preferably 5g / L to 40g / L.
10. A cylindrical device with a grid, used in the method for preparing a composite slow-release oxygen material as claimed in claim 8 or 9, characterized in that: A grille is arranged on the outer peripheral surface of the cylindrical device, and a matching filter bag is built into the cylindrical device; Preferably, the grid is composed of metal wire grid bars evenly staggered; Further preferably, the grille is composed of grille bars metal wires arranged in parallel and staggered; More preferably, the angle α between the staggered metal wire grid bars of the grid is 0-90°, preferably 30-90°; the spacing L between adjacent metal wires of the grid bars is 0.5-3 cm, preferably 1-2 cm; the width of the grid bars is 0.1-0.5 cm, preferably 0.1-0.2 cm; Preferably, the diameter-to-height ratio D / H of the cylindrical device is 0.1 to 0.5, preferably 0.1 to 0.3; Preferably, both ends of the cylindrical device with the grid are connected; Preferably, the top of the outer peripheral curved surface has an external thread, the bottom of the outer peripheral curved surface has an internal thread, and a plurality of cylindrical devices with grids can be connected by threads; Preferably, the grid bar is a metal wire, preferably, the metal wire is at least one of stainless steel wire, iron wire, copper wire, aluminum wire, titanium wire, etc., preferably stainless steel wire; And / or, the mesh number of the filter bag is 50-500 mesh, preferably 100-300 mesh.
11. Use of the modified oxygen-releasing nanoperoxide for degrading organic pollutants as claimed in any one of claims 1 to 3 and / or the modified oxygen-releasing nanoperoxide prepared by the preparation method of the modified oxygen-releasing nanoperoxide as claimed in any one of claims 4 to 6 and / or the composite slow-release oxygen material as claimed in claim 7 and / or the composite slow-release oxygen material prepared by the preparation method of the composite slow-release oxygen material as claimed in any one of claims 8 to 9 in the remediation of soil and / or groundwater containing organic pollutants.
Citation Information
Patent Citations
Preparation method of oxygen slow release preparation for repairing of contaminated site
CN104560051A
Recyclable oxygen slow release device and preparation method thereof
CN110655191A
Sustained-release nano-calcium peroxide materials, preparation thereof, and method for removing chlorohydrocarbon and / or benzene series from underground water through sustained-release nano-calcium peroxide materials
CN110759319A
Preparation method and application of calcium peroxide composite slow-release agent
CN114105331A
Preparation method of double-response slow-release carbon source for denitrification process of low C / N wastewater
CN116395841A
Cited By
Integrated Fenton-like material as well as preparation method and application thereof
CN122183704A